Are Habitual Hydration Strategies of Female Rugby League Players Sufficient to Maintain Fluid Balance and Blood Sodium Concentration During Training and Match-Play? A Research Note From the Field. Issue 3 (March 2016) - Jones, Ben; Till, Kevin; King, Roderick; Gray, Michael; O'Hara, John
Abstract : Abstract: Jones, B, Till, K, King, R, Gray, M, and O'Hara, J. Are habitual hydration strategies of female rugby league players sufficient to maintain fluid balance and blood sodium concentration during training and match-play? A research note from the field. J Strength Cond Res 30(3): 875–880, 2016—Limited data exist on the hydration status of female athletes, with no data available on female rugby players. The objective of this study was to investigate the habitual hydration status on arrival, sweat loss, fluid intake, sweat Na + loss, and blood [Na + ] during field training and match-play in 10 international female rugby league players. Urine osmolality on arrival to match-play (382 ± 302 mOsmol·kg −1 ) and training (667 ± 260 mOsmol·kg −1 ) was indicative of euhydration. Players experienced a body mass loss of 0.50 ± 0.45 and 0.56 ± 0.53% during match-play and training, respectively. During match-play, players consumed 1.21 ± 0.43 kg of fluid and had a sweat loss of 1.54 ± 0.48 kg. During training, players consumed 1.07 ± 0.90 kg of fluid, in comparison with 1.25 ± 0.83 kg of sweat loss. Blood [Na + ] was well regulated (Δ−0.7 ± 3.4 and Δ−0.4 ± 2.6 mmol·L −1 ), despite sweat [Na + ] of 47.8 ± 5.7 and 47.2 ± 6.3 mmol·L −1 during match-play and training. The findings of this study show mean blood [Na + ] that seems to be well regulated despite losses of Na + in sweat and electrolyte-free fluid consumption. For the duration of the study, players did not experience a body mass loss (dehydration >2%) indicative of a reduction in exercise performance, thus habitual hydration strategies seem adequate. Practitioners should evaluate the habitual hydration status of athletes to determine whether interventions above habitual strategies are warranted.